2014
DOI: 10.1038/eye.2013.300
|View full text |Cite
|
Sign up to set email alerts
|

Microincision cataract surgery combined with vitrectomy: a case series

Abstract: Aim The objective of this study was to present the results of combined phacovitrectomy using 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 15 publications
3
20
0
2
Order By: Relevance
“…In a case series of C‐MICS and vitrectomy, Jalil et al. () secured the corneal incision in 11 of 52 eyes, mostly due to a learning curve and a suspected instability of the AC during subsequent vitrectomy. In the present study, none of the eyes from the C‐MICS group required suturing of the corneal wound in accordance with our previous findings, which indicated that 1.8‐mm corneal incision offers very good AC stability, even under excessive manipulation of the globe during surgery (Czajka et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a case series of C‐MICS and vitrectomy, Jalil et al. () secured the corneal incision in 11 of 52 eyes, mostly due to a learning curve and a suspected instability of the AC during subsequent vitrectomy. In the present study, none of the eyes from the C‐MICS group required suturing of the corneal wound in accordance with our previous findings, which indicated that 1.8‐mm corneal incision offers very good AC stability, even under excessive manipulation of the globe during surgery (Czajka et al.…”
Section: Discussionmentioning
confidence: 99%
“…; Jalil et al. ). In a retrospective study, we previously demonstrated the feasibility of the combined C‐MICS and 23G vitrectomy (Czajka et al.…”
Section: Introductionmentioning
confidence: 97%
“…Помутнение задней капсулы Помутнение задней капсулы в послеоперационном периоде обусловлено рядом факторов, таких как боль-ший объем хирургических манипуляций и более выра-женный воспалительный процесс (что неизбежно сопут-ствует комбинированным вмешательствам), тампонада полости стекловидного тела газовой смесью на длитель-ный срок и необходимость для пациента лежать лицом вниз после операции [16][17].…”
Section: осложненияunclassified
“…Показано, что фибри-нозная реакция во влаге передней камеры чаще возникает на фоне увеита и отслойки сетчатки, после эндолазеркоа-гуляции сетчатки и на фоне тампонады полости стекло-видного тела газом и силиконовым маслом [17,22].…”
Section: осложненияunclassified
“…Due to the increase of this day by day, the incidence of cataract will appear. Then there will be surgery of cataract need [22].…”
Section: Introductionmentioning
confidence: 99%